Evaluation of a Novel Method Using Computed Tomography to Predict New Onset of Atrial Fibrillation or Embolic Events after Transcatheter Aortic Valve Implantation: the Role of Hounsfield Unit Density Ratio in the Left Atrial Appendage - Angelillis, Marco; Costa, Giulia; Panico, Roberta Antonazzo; Grigoratos, Chrysanthos; Giannini, Cristina; Fiorelli, Francesca; Spontoni, Paolo; Stazzoni, Laura; Carlo, Marco De; Pedrinelli, Roberto; Son, Anna (Cardiology and Cardiovascular Medicine, 2019)
Backgrounds: Evaluation of left atrial appendage (LAA) with angio-computed tomography (CCTA) in order to predict new onset of atrial fibrillation (AF) or embolic events is a new upcoming topic. No previous reported studies are available in patients undergoing transcatheter aortic valve implantation (TAVI). Methods: We analyzed pre-procedural CCTA scans of 325 patients who underwent TAVI performing a linear coefficient of attenuation analyses with Hounsfield units (HU) in LAA. HU in LAA distal and proximal was calculated, as well as the ratio. A sensibility and specificity analyses was conducted in order to identify the optimal cutoff to predict new onset AF or embolic events after TAVI. Results: Patients were divided into 4 groups according to the presence of AF. Baseline clinical and echocardiographic features were similar except for a significantly higher STS score and mitral regurgitation severity in PRE-TAVI AF group (p=0.003 and p=0.002 respectively). HU analyses showed a statistical difference in measure performed in LAA distal and in the HU LAA distal/Proximal ratio, with the lowest value in patients with pre-TAVI AF (p<0.001 and p<0.001 respectively). The ROC analyses found 0.84 as the cut-off for to predict the composite endpoint of new AF or embolic events, with sensitivity of 51% and specificity of 52% (p=0.008). Conclusion: In patients with aortic stenosis (AS), use of LAA assessment with CCTA to predict embolic events or new onset AF is no efficacy and cannot be substituted clinical indications for prevention and therapy of embolic events.